Effects of Positive End-Expiratory Pressure on Lung Recruitment, Respiratory Mechanics, and Intracranial Pressure in Mechanically Ventilated Brain-Injured Patients - Robba, Chiara; Ball, Lorenzo; Nogas, Stefano; Battaglini, Denise; Messina, Antonio; Brunetti, Iole; Minetti, Giuseppe; Castellan, Lucio; Rocco, Patricia R. M.; Pelosi, Paolo (Frontiers in Physiology, 2021)
Background: The pathophysiological effects of positive end-expiratory pressure (PEEP) on respiratory mechanics, lung recruitment, and intracranial pressure (ICP) in acute brain injured patients have not been completely elucidated. The primary aim of this study was to assess the effects of PEEP augmentation on respiratory mechanics and quantitative computed lung tomography (qCT) findings, as well as its relationship with ICP modifications. Secondary aims included the assessment of the correlations between different factors (including respiratory mechanics and qCT features) with the changes of ICP, and how these factors at baseline may predict ICP response after greater PEEP levels. Methods: Prospective, observational study, including mechanically ventilated patients with acute brain injury requiring invasive ICP and who underwent two-PEEP levels lung CT scan. Respiratory system compliance (Crs), arterial partial pressure of carbon dioxide (PaCO2), mean arterial pressure (MAP), data from qCT and ICP were obtained at PEEP 5 and 15 cmH2O. Results: Sixteen examinations (including double PEEP lung CT and neuromonitoring) in 15 patients were obtained. The median age of the patients was 54 years [interquartile range, IQR= 39-65] and 53% were males. The median Glasgow Coma Scale (GCS) at Intensive Care Unit admission was 8 [IQR=3-12]. Median alveolar recruitment was 2.5 % of total lung weight [-1.5- 4.7]. PEEP from 5 to 15 cmH2O increased ICP (median values from 14.0 [11.2-17.5] to 23.5 [19.5-26.8] mmHg, p<0.001, respectively). The amount of recruited lung tissue on CT was inversely correlated with the change (Δ) in ICP (rho= -0.78; p= 0.0006). Additionally, ΔCrs (rho=-0.77, p=0.008), ΔPaCO2 (rho= 0.81, p=0.0003) and ΔMAP (rho= -0.64, p=0.009) were correlated with ΔICP. Baseline Crs was not predictive of ICP response to PEEP. Conclusions: The main factors associated with increased ICP after PEEP augmentation included reduced Crs, lower MAP and lung recruitment, as well as increased PaCO2, but none of these factors were able to predict, at baseline, ICP response to PEEP. In order to assess the potential benefits of increased PEEP in patients with acute brain injury, hemodynamic status, respiratory mechanics, and lung morphology should be taken into account.